PEMBUATAN FATLIQUOR DARI CAMPURAN MINYAK SAWIT DAN KEDELAI - Herry Suseno; Sri Sumarni; M.W. Syabani (Politeknik ATK Yogyakarta, 2014)
Fatliquoring is one of important processes in leather tanning. Its main process function is to keep the quality of leather, especially on organoleptical test. The aim of this research is to study the blend of palm oil and soybean oil (1:1 ratio) as fatliquor raw materials. Palm oil was chosen because Indonesia has abundant material and also is one of main players in palm plantation and production. At the beginning, the raw material is analyzed to determine the quality, i.e. acid number, saponification number, iod number and fatty acid contains. Then the raw material is processed to be fatliquoring agent with sulfitation process. The fatliquoring agent was then analyzed to determine its quality and applied in fatliquoring leather. Finally, the leather mechanical characteristics were tested, i.e. tensile, elongation and stitch strengths. The result gives information that the application of fatliquor makes the leather have better test parameter. The value of tensile, elongation and stitch strengths for leather without fatliquor 160 kg/cm2, 63% and 82 kg/cm; and for leather with fatliquor 250 kg/cm2, 142% and 163 kg/cm. Therefore, fatliquoring agent made from palm oil and soybean oil blend can be used as alternative material in fatliquoring process.